FRAMEWORK ON CRITICAL SUCCESS FACTORS AFFECTING ON MAINTENANCE MANANGEMENT AND PRACTICE IN PUBLIC PROJECT - AZAHARI, FATIN AZUREEN (Universiti Teknologi PETRONAS, 2017)
In Malaysia, most of the company faced problems in conducting effectiveness maintenance due to unclear plan and unsystematic approach. Improper maintenance management and practices could affect the performance levels of the maintenance works and the productivity of the building. Therefore, research is needed in order to minimize the issues. This research has been conducted with the objective to identify and rank the factors influencing the effective maintenance activities based on the Relative Importance Index (RII) and correlation between operations managers, site engineers and technicians, validate the maintenance management and practice using project case study and to develop a framework for the maintenance personnel. Thus, in order to achieve the purpose of the research, data gathering by distributing questionnaires and interview sessions with 35 maintenance personnel and critical analysis of previous papers related to maintenance management has been conducted. For data analysis, about 89.7% questionnaires were valid.